5-(4-Bromo-2-nitrophenyl)-1,3,4-thiadiazol-2-amine - Zhang, Jian-qiang (International Union of Crystallography, 2011)
The title compound, C(8)H(5)BrN(4)O(2)S, was synthesized by the reaction of 4-bromo-2-nitrobenzoic acid with thiosemicarbazide. The dihedral angle between the thiadiazole and benzene rings is 40.5 (2)°. In the crystal, the strongest N—H⋯N intermolecular hydrogen bond, between the amine group and one thiadiazole N atom, forms centrosymmetric dimers. The other amine H atom extends the supramolecular network, forming an N—H⋯N contact with the other thiadiazole N atom.